VIDEOS & FILMS - Goodney-Lea, Suzanne (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
VIDEOS & FILMS NOTE: For those items with an asterisk after the title, an assignment/exercise sheet can be found in the Exercises/Assignments/Activities section of this guide. I have not provided purchasing information for feature films, as these are generally quite easy to find.